PENGARUH TATA KELOLA PEMERINTAHAN, EFEKTIVITAS PENGENDALIAN INTERNAL, PERAN AUDITOR INTERNAL, DAN KETAATAN ATURAN AKUNTANSI TERHADAP PENCEGAHAN KECURANGAN (Studi Empiris Pada SKPD Provinsi Riau) - Oktavia, Tiara; Taufik, Taufeni; A, Al Azhar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The study aimed to analyze the effect of good govenance, the effectiveness of internal control, role of internal auditors, and the obedience of accounting rules to the fraud prevention. Sampling technique used is purposive sampling. Object of this research is SKPD of Riau Provinces with the sample 93 respondents. Statistical method used to test the hypothesis of the research is multiple linear regression analysis and using Statistical Product and Service Solution (SPSS) software version 21.0.The results of this research showed good governance has an effect to the fraud prevention with dirrect effect 0,002 significance, the effectiveness of internal contor has an effect to the fraud prevention with direct effect 0,016 significance, role of internal auditors has an effect to the fraud prevention with direct effect 0,004 significance and the obedience of accounting rules has an effect to the fraud prevention wit direct effect 0,000 significance. Based on the research it was concluded that the determination coefficient (R2 ) is 0,620. It means that 62% of the fraud prevention can be explained by the variable good govenance, the effectiveness of internal control, role of internal auditors and the obedience of accounting rules. While 38% is explained by other variables.Keywords: good govenance, the effectiveness of internal control, role of internal auditors,the obedience of accounting rules, fraud prevention.